Study of the intracellular nanoparticle-based radiosensitization mechanisms in F98 glioma cells treated with charged particle therapy through synchrotron-based infrared microspectroscopy - Martínez-Rovira, Immaculada; Seksek, Olivier; Dokić, Ivana; Brons, Stephan; Abdollahi, Amir; Yousef, Ibraheem (The analyst, 2020)
The use of nanoparticles (NP) as dose enhancers in radiotherapy (RT) is a growing research field. Recently, the use of NP has been extended to charged particle therapy in order to improve the performance in radioresistant tumors. However, the biological mechanisms underlying the synergistic effects involved in NP-RT approaches are not clearly understood. Here, we used the capabilities of synchrotron-based Fourier Transform Infrared Microspectroscopy (SR-FTIRM) as a bio-analytical tool to elucidate the NP-induced cellular damage at the molecular level and at a single-cell scale. F98 glioma cells doped with AuNP and GdNP were irradiated using several types of medical ion beams (proton, helium, carbon and oxygen). Differences in cell composition were analyzed in the nucleic acids, protein and lipid spectral regions using multivariate methods (Principal Component Analysis, PCA). Several NP-induced cellular modifications were detected, such as conformational changes in secondary protein structures, intensity variations in the lipid CHx stretching bands, as well as complex DNA rearrangements following charged particle therapy irradiations. These spectral features seem to be correlated with the already shown enhancement both in the DNA damage response and in the reactive oxygen species (ROS) production by the NP, which causes cell damage in the form of protein, lipid, and/or DNA oxidations. Vibrational features were NP-dependent due to the NP heterogeneous radiosensitization capability. Our results provided new insights into the molecular changes in response to NP-based RT treatments using ion beams, and highlighted the relevance of SR-FTIRM as a useful and precise technique for assessing cell response to innovative radiotherapy approaches.